(untitled) (Scientific journal of the Fergana State University, 2023)
The article explores the essence and integrative function of the National idea, the socio-spiritual, political and historical foundations of the idea of ensuring the ideological unity of the people at a new stage of development of Uzbekistan, its implementation on the basis of the idea of national rise.